A Study to Assess the Effectiveness of Self-Instructional Module on Knowledge of Electrocardiogram Among Staff Nurse in a Selected Hospital in Mahagaon - Shastri Neha M.; Borkar Aleen; Eppalwar Sunita; Sambaragi S. Vijay (International Journal of Evidence Based Nursing And Practices, 2025)
Objectives: This study aimed to evaluate the staff nurses' knowledge of electrocardiograms (ECG) and to determine the impact of a structured teaching program in improving their understanding of the subject. Methodology: An evaluative research design was employed for this study. The study involved 22 staff nurses chosen through simple random sampling and was carried out at Sant Gajanan Maharaj Rural Hospital, Mahagaon. A structured knowledge questionnaire was used to gather data, followed by a structured teaching program. The collected data were analysed using descriptive and inferential statistics in alignment with the study objectives. Results: The demographic analysis revealed that the majority of staff nurses (15%) were aged between 21 and 23 years, with 90% belonging to the Hindu religion, and 70% were females. Additionally, 75% of the participants had prior knowledge of ECG. In the pre-test, most staff nurses had some basic knowledge regarding electrocardiograms. Following the structured teaching program, a notable enhancement in their knowledge was observed. Post-test results showed that 90% of the nurses gained adequate knowledge, while 10% showed moderate knowledge. The mean post-test knowledge score was 13.85, with a standard deviation of 2.37, compared to a mean pre-test score of 6.7, reflecting a significant increase in knowledge with a mean difference of 7.15. The paired t-test result was t=29.3511, p=0.005. The improvement was statistically significant, demonstrating the effectiveness of the structured teaching program in enhancing the participants' knowledge. Additionally, no significant relationship was identified between the pre-test knowledge scores and the demographic variables. Conclusion: The study concluded that the structured teaching program was highly effective in improving the knowledge of staff nurses regarding electrocardiograms. The program successfully increased their understanding and competence in ECG interpretation, emphasizing the importance of such educational interventions in healthcare settings.
Keywords: Electrocardiogram (ECG); evaluative research design; knowledge assessment; staff nurses; structured teaching program